Primary healthcare and child and maternal health in the Middle East and North Africa (MENA): A retrospective analysis of 29 national survey data from 13 countries - Zlatko Nikoloski; Hrayr Wannis; Leonardo Menchini; Anirban Chatterjee (Elsevier, 2021)
The objective of this paper is three-fold: (i) to analyse the coverage and equity of access to selected maternal and child healthcare interventions, particularly those delivered in Primary Healthcare (PHC) setting; (ii) to analyse the main drivers of inequitable access to selected interventions; and (iii) to synthesise and compare the results across the Middle East and North Africa (MENA) region as well as over time. We analysed data for five key maternal and child healthcare interventions from 29 national surveys (DHS and MICS) covering 13 MENA countries and spanning a period of almost 20 years (2000-2018). We calculated coverage indicators, concentration indices (CI) and decomposition of CIs according to standard definitions. We synthetized the results by country groups based on their human development index (HDI). Over time and among countries that started from a lower base, there has been an improvement in coverage and equity of selected interventions (four ante-natal care visits and skilled birth assistance). When considering the place of skilled delivery, there is a clear rich-poor divide, with women from richer wealth quintiles gravitating toward private healthcare facilities and those from poorer wealth quintiles toward public ones. While most of the care-seeking for common child illnesses occurs in PHC facilities, a fraction (20-30 percent) of care-seeking takes place in secondary healthcare facilities. PHC has played a role in improving coverage and equity of access in key maternal and child health interventions in the wider MENA region. Better integration of care, strengthening and improving the PHC network could increase the use of cost-effective interventions, which are key to improving maternal and child health.